2008
DOI: 10.1002/pro.18
|View full text |Cite
|
Sign up to set email alerts
|

A green fluorescent protein screen for identification of well‐expressed membrane proteins from a cohort of extremophilic organisms

Abstract: Green fluorescent protein (GFP) fusion proteins provide a potentially facile tool for identification of well expressed, properly behaved membrane proteins for biochemical and structural study. Here, we present a GFP-expression survey of >300 membrane proteins from 18 bacterial and archaeal extremophiles, organisms expected to be rich sources of membrane proteins having robust biophysical properties. We find that GFP-fusion fluorescence intensity is an excellent indicator of over-expression potential. By employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…Building upon previously described reports using GFP as a reporter for monitoring expression and purification, [3][4][5][6][7][8][9][10][14][15][16] we established a comprehensive, streamlined approach for confirming topology, optimizing expression, and screening stable protein-detergent complexes for both C in and C out membrane proteins. The pWarf vector system consists of two vectors, pWarf(À) and pWarf(þ), that were constructed by modifying the pET28 vector described in Drew et al 9 (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon previously described reports using GFP as a reporter for monitoring expression and purification, [3][4][5][6][7][8][9][10][14][15][16] we established a comprehensive, streamlined approach for confirming topology, optimizing expression, and screening stable protein-detergent complexes for both C in and C out membrane proteins. The pWarf vector system consists of two vectors, pWarf(À) and pWarf(þ), that were constructed by modifying the pET28 vector described in Drew et al 9 (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have employed GFP as a reporter for membrane protein expression and detergent selection, [3][4][5][6]9,10,14,15 but the technology has largely been restricted to proteins with intracellular C-termini (C in ) due to the GFP's inability to mature when localized to the E. coli periplasm. 11 We have demonstrated that Glycophorin A (GpA)-a single spanning transmembrane helix-effectively converts C out membrane proteins to become C in proteins where the GFP can properly fold and fluoresce.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, this protocol can further be adapted for purification of recombinant GFP-fusion proteins, in which an unrelated target protein is "tagged" with GFP. GFP-tagged target proteins can be detected with UV light 11 and purified using various chromatographic approaches, including the HIC purification strategy described above. GFP purification has also become a pedagogical staple in biochemistry labs for the teaching of modern protein science techniques 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of GFP Relative Fluorescence Intensity in E. coli GFP-fusion fluorescence intensity was an excellent indicator of over-expression potential [30]. Because fluorescence was one of the most convenient ways to follow a protein expression and purification procedure [31], so the fluorescence intensity was used to analyze the expression efficiency of proteins.…”
Section: A Constructions Of Plasmid and Cloning Vectorsmentioning
confidence: 99%